Stress strain state of double-layered ferrocement shells under the fire condition - A. V. Zhurtov; T. A. Khezhev; G. N. Khadzhishalapov; A. A. Kardanov; M. A. Shogentsukov (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. Development of a method for calculating the bearing capacity of twolayer reinforced cement shells for force and temperature effects in a fire. These structures consist of a fire-retardant layer made of vermiculite concrete, as well as a carrier layer of fine-grained concrete reinforced with mesh.Method. The solution is carried out in a physically nonlinear formulation using the deformation theory of concrete plasticity by G.A. Geniev. In obtaining the resolving equations, the theory of shallow shells by V.Z. Vlasov is used. The physically nonlinear problem reduces to the sequential solution of elastic problems for a structure whose physicomechanical parameters are functions of the x, y, z coordinates. The solution is carried out by the finite element method in combination with the Newton-Raphson method. The dependence of the characteristics of construction materials on temperature is taken into account. The temperature field is assumed to be a function of only one z coordinate, and the finite difference method is used to determine it.Result. the results of numerical simulation of full-scale experiments in a fire chamber for single-layer and two-layer shells are presented. Some deviations are revealed, caused on the one hand by inaccuracies of the experiment and errors of the theory on the other hand.Conclusion. A significant influence of the boundary conditions on the process of deformation of the structure was found. When the support contour was fixed along x and y, a shell bend up was observed, which was consistent with experimental data, and in the case of a freely sliding support contour, the structural points moved exclusively downward. In general, the agreement between the results and experimental data is quite good, which allows us to use the methodology for calculating real structures.